THE DECADENCE OF MORALITY THROUGH MODERNISATION: THE ANALYSIS OF REGRETS OF THREE ROMANTIC POETS - Zulkifli, Che Nooryohana; Mohamad Putera Idris; Ahmad Zubir, Hanani; Aboo Bakar, Rofiza (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The romantic era began when the fact that there were many poets and writers had published their works focusing on the enlightenment of knowledge. Most of them welcomed Romanticism as the dawn of modernisation; appraising knowledge in the areas of science, music, and literature (Cunningham & Jardine, 1990). Despite there were a number of poets in this era produced notable works in the literature which have directed their writing to celebrate modernisation, the very few pieces of works which appeared to defy the existence of modern world must also be addressed. Thus this paper delves into the concept of exploring the negativities of modernisation which in one way or another have affected the nature of humans and their humanity that has been foreseen and felt by three selected Romantic poets namely William Wordsworth, William Blake, and Robert Frost. This paper has therefore selected three poems written by these three respective poets to identify the exact areas which are believed to carry their mood of dejection about this era of industrialism and cultural transformation. The results of the analysis have shown that this era, despite the ease it had offered in enhancing people’s lifestyles and economy, the poets chose to persevere with their stance by showing their reproach towards the modern world through their poems.